The future of Evo‐Devo: the inaugural meeting of the Pan American Society for evolutionary developmental biology. Issue 2 (15th January 2016) - Lesoway, Maryna P.
SUMMARY: What is the future of evolutionary developmental biology? This question and more were discussed at the inaugural meeting for the Pan American Society for Evolutionary Developmental Biology, held August 5−9, 2015, in Berkeley, California, USA. More than 300 participants attended the first meeting of the new society, representing the current diversity of Evo‐Devo. Speakers came from throughout the Americas, presenting work using an impressive range of study systems, techniques, and approaches. Current research draws from themes including the role of gene regulatory networks, plasticity and the role of the environment, novelty, population genetics, and regeneration, using new and emerging techniques as well as traditional tools. Multiple workshops and a discussion session covered subjects both practical and theoretical, providing an opportunity for members to discuss the current challenges and future directions for Evo‐Devo. The excitement and discussion generated over the course of the meeting demonstrates the current dynamism of the field, suggesting that the future of Evo‐Devo is bright indeed.